Green Banking Perspektif Maqāṣid Asy-Syarīʿah dalam Mendorong Eksistensi Perbankan Syariah - Nurjannah, Nurjannah; Lince Bulutoding; Nasrullah Bin Sapa; Amiruddin K; Sumarlin Sumarlin (Al-Buhuts, 2024)
This study aims to describe the implementation of green banking from the perspective of maqāṣid asy-syarīʿah in encouraging the existence of Islamic banking. This study is a qualitative study using a phenomenological approach, an interpretive paradigm using intentional analysis. The types of data used are noema and noesis, using three data collection techniques, namely in-depth interviews, documentation and participant observation. The results of the study indicate that the implementation of green banking based on maqāṣid syarī᷾ah is able to encourage the existence of Islamic banking. The implementation of green banking from the perspective of maqāṣid asy-syarīʿah at Bank Muamalat Indonesia and Bank Syariah Indonesia in supporting its existence consists of seven components, maintaining religion (ḥifẓ al-dīn), maintaining the Soul (ḥifẓ al-nafs), maintaining the environment (ḥifẓ al-bī᷾ah), and maintaining honor (ḥifẓ al-irdi) have been implemented, while maintaining reason (ḥifẓ al-᷾aql) requires improvement in green banking research and publication, maintaining descendants (ḥifẓ al-᷾nasl) requires improvement in terms of digital banking system security and the presence of product innovation, and maintaining wealth (ḥifẓ al-māl) requires providing opportunities for farmers to be able to apply for financing using the salam contract or other related contracts.